(Re)visions télévisuelles de la colonisation du Nord – série médiatique d’Un homme et son péché de Claude-Henri Grignon - Wójcik, Katarzyna (Romanica Silesiana, 2020)
Claude-Henri Grignon’s novel Un homme et son péché presents the life of French Canadian colonial settlers of the Laurentides region at the end of XIXth century. It depicts a realistic image of the colonisation period of Quebec history. The novel is at the origin of a media series that englobes a radio adaptation, three filmic adaptations, theater adaptations, a comic, and two television series. The aim of this article is to discuss the vision of colonisation by analysing two television series based on Un homme et son péché: Les Belles Histoires des pays d’en haut broadcast from 1956 to 1970 and Les Pays d’en haut broadcast from 2016 to 2019 on ICI Radio-Canada Télé 1. The analysis will try to trace modifications inherent to the process of adaptation on different levels (protagonists, representation of space, ideological discourse) and their influence on the vision of the colonisation period.